Toward an Integrated View of Investor Behavior: A Bibliometric Study on Financial Literacy and Psychological Biases - Pradana, Novta Winkey (Journal of Financial and Behavioural Accounting, 2025)
This study investigates the intersection between financial literacy and behavioral biases in investment decision-making, addressing the limited theoretical and empirical integration between the two domains. Adopting a quantitative bibliometric design, data were collected from 1,000 peer-reviewed journal articles indexed in CrossRef (2014–2025) using Publish or Perish, with purposive sampling based on metadata relevance. The dataset was analyzed using VOSviewer, which produced three core visualizations—network, overlay, and density—to map the intellectual structure, thematic development, and research intensity. The findings reveal four major clusters: financial literacy, behavioral biases, digital innovation, and empirical approaches. Financial literacy emerges as the cognitive foundation of investor behavior, while biases such as overconfidence and herding impede rational decision-making—especially in digital contexts and among younger generations. The study concludes that a cross-domain approach is essential for comprehensively understanding contemporary investment behavior. It recommends integrating technology-driven financial education with behavioral awareness to inform more inclusive and adaptive policy and market interventions.